The Influence of Parents' Communication Intensity on Learning Outcomes of STKIP Pembangunan Indonesia Makassar Students - Nur Astaman Putra; Khaidarsyah Khaidarsyah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
The success or failure of education in schools depends on and is influenced by education in the family. The purpose of this study was to determine the effect of parental communication intensity on student learning outcomes in the Economic Education Study Program of STKIP Pembangunan Indonesia Makassar. The research was conducted with a quantitative approach using an analytical research design. The study population was all economic students of STKIP Pembangunan Indonesia Makassar with a population of 604 students. After taking the sample using the sample size calculator, the total sample size was 264 students. This study using an accidental sampling dam due to the pandemic period so that this research instrument uses an online questionnaire which is distributed to students using the help of the google form application. The variable intensity of parental communication assessed by several indicators, namely frequency, duration, attention, regularity, level of breadth, and level of depth which were then divided into two categories, namely high and low. Meanwhile, the learning outcome variable is measured based on the GPA of the students. The data were analyzed using a simple linear regression test to see the effect of communication intensity on student learning outcomes. Analysis of using statistical software. The results of the study found that low communication intensity was in line with unsatisfactory GPA scores and conversely, high communication intensity was in line with satisfactory GPA scores. Analysis with a simple linear regression test with a significance level of 95% found a p-value of 0.04 smaller than 0.05, meaning that there was an influence on the intensity of parental communication on student learning outcomes of the economic education study program STKIP Pembangunan Indonesia Makassar